2021
DOI: 10.1126/scisignal.abc1983
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus induces β 2 -adrenergic receptor dysfunction in human airway smooth muscle cells

Abstract: Pharmacologic agonism of the β2-adrenergic receptor (β2AR) induces bronchodilation by activating the enzyme adenylyl cyclase to generate cyclic adenosine monophosphate (cAMP). β2AR agonists are generally the most effective strategy to relieve acute airway obstruction in asthmatic patients, but they are much less effective when airway obstruction in young patients is triggered by infection with respiratory syncytial virus (RSV). Here, we investigated the effects of RSV infection on the abundance and function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Postnatally, pharmacologic agonism of β2ARs typically induces bronchodilation by activating the adenylyl cyclase and generating cyclic adenosine monophosphate (cAMP), which in turn mediates smooth muscle relaxation through protein kinase A (PKA)-dependent mechanisms. However, we have recently shown that RSV infection results in proteolytic cleavage of β2AR, non-canonical activation of adenylyl cyclase impairing cAMP synthesis, and increased muscle contractility due to higher cytosolic calcium concentration, with the net effect of favoring airway obstruction and reducing the bronchodilator effect of β2AR agonists [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postnatally, pharmacologic agonism of β2ARs typically induces bronchodilation by activating the adenylyl cyclase and generating cyclic adenosine monophosphate (cAMP), which in turn mediates smooth muscle relaxation through protein kinase A (PKA)-dependent mechanisms. However, we have recently shown that RSV infection results in proteolytic cleavage of β2AR, non-canonical activation of adenylyl cyclase impairing cAMP synthesis, and increased muscle contractility due to higher cytosolic calcium concentration, with the net effect of favoring airway obstruction and reducing the bronchodilator effect of β2AR agonists [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…RSV virus activity and load are related to the severity of the disease and also determine the degree of inflammation [ 18 ]. The anti-inflammatory property of NAC was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ß-2AR desensitization occurs in the absence of internalization or degradation of the β2-AR as it results from receptor uncoupling due to phosphorylation by GRK2 ( 60 ). More recently, Harford et al ( 61 ) investigated the density and activity of ß-2AR in primary HASM cells derived from pediatric lung tissue with RSV infection compared to non-infected control cells. Their findings showed that RSV induced simultaneously more effects, including a proteasome-mediated cleavage of ß-2AR, a ß-2AR ligand-independent activation of adenylyl-cyclase, and a decrease in cAMP release compared to the control cells, and, lastly, increased intracellular concentrations of Ca2+ resulting in ASM cells contraction ( 61 ).…”
Section: Rsv and Immune-pulmonary Pathwaysmentioning
confidence: 99%
“…More recently, Harford et al ( 61 ) investigated the density and activity of ß-2AR in primary HASM cells derived from pediatric lung tissue with RSV infection compared to non-infected control cells. Their findings showed that RSV induced simultaneously more effects, including a proteasome-mediated cleavage of ß-2AR, a ß-2AR ligand-independent activation of adenylyl-cyclase, and a decrease in cAMP release compared to the control cells, and, lastly, increased intracellular concentrations of Ca2+ resulting in ASM cells contraction ( 61 ). Lastly, another explanation for the lack of effectiveness of ß-2AR agonists in infants suffering from RSV infection could be due to the fact that RSV not only induces muscular constriction (bronchospasm) but also impacts the bronchiolar caliber, inducing lymphoid hyperplasia, edema, and mucous plugging, promoting an additional extrinsic compression.…”
Section: Rsv and Immune-pulmonary Pathwaysmentioning
confidence: 99%